STUDI MORFOMETRIK UDANG CENDANA (Metapenaeus brevicornis) YANG TERTANGKAP DI PERAIRAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Nor Aisyah Wardani; Muhammad R. Syahrir; Paulus Taru (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
Yellow Shrimp (M. brevicornis) is a type of shrimp caught by Samboja fishermen which has a fairly high economic value. This study aims to provide information about the morphomorphological study of Yellow Shrimp (M. brevicornis) caught in the waters of Samboja, Kutai Kartanegara. This research was conducted in the waters of Samboja, Kutai Kartanegara, in November-December 2021, the sample used was 300 Yellow Shrimp (M. brevicornis). Morphometric study onmorphometric study Yellow Shrimp (M. brevicornis) using analysis with analysis of covariance test (ANCOVA) to see 20 morphometric covariates that affect total length (PTO). Based on the results of the analysis of the univariate ANOVA test, it is known that 20 morphometrics have a sig value <0.05, which means that H1 is accepted, that all morphometrics have an effect on PTO. Furthermore, ancova analysis was performed, obtained 5 morphometrics that have sig < 0.05, namely head length (PK), first segment length (PRP), telson length (TLS), lower head length (PKB) and tail length (PE), so from the results of the ancova test analysis showed that the most significant morphometric effect on PTO was 5 morphometers.